Synthesis and Crystal Structure of Diethyl Dithiocarbamate Tellurium - QUE, MEI; ZHANG, YU-CHUAN; BING, WU (Asian Journal of Chemistry, 2010)
Diethyl dithiocarbamate tellurium was synthesized and characterized by IR spectra, elemental analysis. and single-crystal X-ray diffraction analysis. The crystal structure of tellurium complex was determined by single-crystal X-ray. The possessing parameters: P2(1)/c, a = 15.1640(3) Å, b = 8.4055(2)Å, c = 14.7887(2)Å, α = 90º, β = 117.228(10)º, γ = 90º, V = 1676.1(6)Å3, Z = 4, Mr = 424.12, Dc = 1.681 g/cm3, μ = 2.256 mm-1, F(000) = 840, T = 296(2)K, R1 = 0.0246, wR2 = 0.0603 for 3799 reflections with I > 2σ(I).